Overactivation of posterior insular, postcentral and temporal regions during preserved experience of envy in autism. (29th January 2023) - Fittipaldi, Sol; Armony, Jorge L.; Migeot, Joaquín; Cadaveira, Matías; Ibáñez, Agustín; Baez, Sandra
Abstract: Social emotions are critical to successfully navigate in a complex social world because they promote self‐regulation of behaviour. Difficulties in social behaviour are at the core of autism spectrum disorder (ASD). However, social emotions and their neural correlates have been scarcely investigated in this population. In particular, the experience of envy has not been addressed in ASD despite involving neurocognitive processes crucially compromised in this condition. Here, we used an fMRI adapted version of a well‐validated task to investigate the subjective experience of envy and its neural correlates in adults with ASD ( n  = 30) in comparison with neurotypical controls ( n  = 28). Results revealed that both groups reported similarly intense experience of envy in association with canonical activation in the anterior cingulate cortex and the anterior insula, among other regions. However, in participants with ASD, the experience of envy was accompanied by overactivation of the posterior insula, the postcentral gyrus and the posterior superior temporal gyrus, regions subserving the processing of painful experiences and mentalizing. This pattern of results suggests that individuals with ASD may use compensatory strategies based on the embodied amplification of pain and additional mentalizing efforts to shape their subjective experience of envy. Results have relevant implications to better understand the heterogeneity of this condition and to develop new intervention targets. Abstract : Social emotions have been scarcely studied in autism spectrum disorder (ASD). We used an fMRI task to investigate the subjective experience of envy in adults with ASD relative to neurotypicals. Although both groups reported similarly intense experience of envy, participants with ASD showed overactivation of the posterior insula, the postcentral gyrus and the posterior superior temporal gyrus, suggesting the use of compensatory mechanisms based on the embodied amplification of pain and additional mentalizing efforts. Results have theoretical and clinical implications.